The physical preparation of players for the Rugby World Cup - Pyne, D. B.; Cook, C. J., Kilduff, L. P. (International Journal of Sports Physiology and Performance, 2023)
The quadrennial showcase of rugby is the Rugby World Cup (RWC), with the 10th Cup being held in France in September and October 2023. The RWC is the third most popular global sporting event after the soccer World Cup and the summer Olympic games. The 2022 Women`s RWC final drew a record crowd of 45,000 in New Zealand. World Rugby has the vision of a global sport for all; it can be played by individuals of all sizes, genders, and abilities. The heart of the game centers on possession of the ball, the expression of free running, and the physicality of tackling and contact.